Analysis of factors that influence students in using Islamic mobile banking - Aditya, Deny Rahmad (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2024)
The study aims to analyze factors that influence the decision of students to use Islamic mobile banking services. In this study, 180 respondents were collected through purposive sampling with criteria that have used or are currently using mobile banks, respondents answered an online survey through Google Forms as the main data collection. The method for analyzing gathered data in this study uses Multiple Linear Regression. The findings show that the factors of Performance Expectancy, Social Influence, and Islamic financial literacy have a positive influence while Risk Vibe has a negative influence. These four variables are significant to the decision to use Islamic mobile banking. These four factors can explain about 57.2% of the intention decision to use Islamic mobile banking services. These findings imply that these factors need to be considered by customers and banks. Islamic banking must continue to strive for security, data confidentiality, and customer trust in more creative, comfortable, and effective mobile banking service features and systems so that customers still feel their decision to use Islamic mobile banking services is correct.